GC/MS Based Phytochemical Analysis of Lichen Species of Acetone extract Pseudevernia furfuraceae (L) Zopf - Mr. Sharad V. Bhandarkar; Mr. Deepak S. Mohale; Mr. Bhojraj T. Satpute (International Journal of Scientific Research in Science and Technology, 2025)
Pseudevernia furfuraceae (L) Zopf (Parmiliaceae) is a common epiphytic lichens in the forest of Navegaon forest of Maharashtra India. the sepsis used as traditionally as a treatment of wounds and eczema The major component of Pseudevernia furfuraceae (L) Zopf after GCMS analysis is 1,3-Dioxolone-4-methanol 2,2dimethyl,, Azaridine-1-(2-methyl-1-propenyl) -(S)- Azaridine-1-(2-methyl-1-propenyl)- E-2-Hexenyl E-2-Octenoate.
Keywords: Pseudevernia furfuraceae L Zopf. P.F.; Retention time R.T.